Efek Kombinasi Back Massage dan Acupoint Massage terhadap Peningkatan Kadar Prolaktin - Asmalinda, Wita; Lestari, Dian (Jurnal Kesehatan, 2020)
Stimulation of the nipples can be done with acupoint massage at the acupressure points around the breast. Acupoint massage therapy can help maximize prolactin and oxytocin receptors and minimize the side effects of late breastfeeding by babies. Back Massage at the meridian point will activate the release of endorphins hormone which has an effect on the sense of comfort and relax in the mother so that an increase in milk production. The aims of this research to know the effects of a combination of Back massage and Acupoint massage on increasing prolactin levels. This type of research is experimental epidemiology with a comparison group (post-test only with control group design). This research was conducted at BPM Meli Rosita for 3 months. The sample in this study was postpartum women who met the inclusion and exclusion criteria. A sample size of 34 people. The measurement parameter had an increase in prolactin. Which included at homogeneity test sample using the Kolmogorov-smirnov test, description analysis to know to mean value, and standard deviation. There was a significant increase in the number of prolactin. The combination of back massage and Acupoint massage affects the increase prolactin level.